OBSERVING TEACHER’S STRATEGIES IN TEACHING READING NARRATIVE TEXT FOR THE TENTH GRADERS - Yeni Fitriana; Happy Kusuma Wardani (Relawan Jurnal Indonesia, 2024)
Reading is crucial for students’ academic endeavors because it helps students in getting knowledge. With the increasing demand for reading proficiency, students often encounter difficulties in comprehending English texts. This study aims to investigate the teaching strategies employed by an English teacher in reading narrative text for the tenth graders of MA Ma’arif NU Assa’adah Bungah Gresik and the student's responses to the strategies. An English teacher who taught in the tenth grade along with 24 tenth graders of MA Ma’arif NU Assa’adah Bungah became the subjects of this research. By employing a mixed-method research design, the observation sheet was utilized as a qualitative instrument to note down the results of observation in the teaching-learning process, whereas the questionnaire was utilized as a quantitative instrument to find out the students’ responses to the teacher’s strategies in teaching reading Narrative Text. Descriptive qualitative and descriptive statistics in the form of percentages were used to analyze the data. Through three sessions of observation, it revealed that the teacher employed various strategies in teaching reading of narrative text including Scanning, Skimming, Guessing, Silent Reading, Question and Answer Relationship (QAR), Think Aloud, and Jigsaw strategy. Meanwhile, the results of the questionnaire depicted positive responses from students. It indicated that the students perceived benefits from the teacher’s strategies in facilitating comprehension and engagement.